Oral Health Care in Greece: A Structured Evidence Synthesis and Health-System Mapping of Access, Financing, Workforce, and Quality Measurement - Maria Gamvrouli; Christos Triantafyllou; Vion Psiakis; Joao Breda (Oral, 2026)
Background/Objectives: Oral diseases are common, largely preventable and closely associated with social determinants, noncommunicable diseases and quality of life. Greece has historically had a high dentist-to-population ratio; however, oral health care remains highly dependent on private provision and out-of-pocket payment. This structured evidence synthesis and health-system mapping aims to summarize the current situation of oral health care in Greece, focusing on access, financing, workforce capacity, epidemiology, prevention, and quality measurement. Methods: A structured evidence synthesis and health-system mapping were conducted using publicly available and verifiable sources, including World Health Organization documents, OECD/European Observatory country health profiles, Eurostat data, official Greek government information, and peer-reviewed studies identified through PubMed, Google Scholar, publisher records, and reference-list searching. The final synthesis included 29 sources: 15 peer-reviewed articles and 14 official or institutional documents/data sources. A formal systematic review, with or without meta-analysis, was not methodologically feasible because the research question was not based on a single intervention, exposure, comparator, or outcome, and because key evidence on oral health-system organization, financing, and governance is contained in heterogeneous policy documents, administrative sources, official reports, and country profiles that are not consistently indexed in bibliographic databases. Evidence was organized across predefined health-system domains: governance, service delivery, financing, workforce, epidemiology, equity, information systems, and quality measurement. Results: Greece combines high dentist density with limited public dental coverage and major financial barriers. Current EOPYY rules list age-specific preventive and treatment benefits, and Dentist Pass provided a preventive dental-care voucher for children; however, no ring-fenced national dental-treatment allocation or nationwide uptake estimate was identified. Most routine adult dental care remains privately financed. Recent Eurostat data indicate that Greece has the highest reported unmet dental care needs in the European Union. Comparative WHO country-profile indicators suggest that Greece’s high dentist density does not, by itself, correspond to lower unmet dental care needs or stronger publicly reported coverage of routine and preventive oral health care. Epidemiological studies show persistent caries, periodontal disease and tooth loss, particularly among children, older adults and socioeconomically disadvantaged groups. Major system-level gaps include limited financial protection, weak integration with primary care, insufficient standardized referral pathways and limited routine measurement of oral health quality and outcomes. Conclusions: The findings suggest that strengthening oral health care in Greece would require a shift from fragmented, curative and privately financed care toward prevention-oriented, publicly accountable and measurable services integrated with universal health coverage and national quality-of-care reforms.